2012
DOI: 10.1080/09602011.2012.676284
|View full text |Cite
|
Sign up to set email alerts
|

Development of a motivational interviewing programme as a prelude to CBT for anxiety following traumatic brain injury

Abstract: A brief preparatory programme, based on the principles of motivational interviewing (MI), was developed as a way of engaging clients with traumatic brain injury (TBI) and preparing them for a cognitive behaviour therapy (CBT) programme for anxiety. The MI + CBT programme was delivered to a male client in his early 40s with severe TBI at four months post-injury, using a single-subject design with repeated measures pre- and post-treatment. The client received three sessions of manualised MI, followed by nine ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…MI sessions were guided by Westra & Dozois (2003) using a study specific manual detailed elsewhere (Hsieh et al 2012 c ). Sessions were designed to facilitate treatment engagement and expectancy using core strategies and principles of MI.…”
Section: Methodsmentioning
confidence: 99%
“…MI sessions were guided by Westra & Dozois (2003) using a study specific manual detailed elsewhere (Hsieh et al 2012 c ). Sessions were designed to facilitate treatment engagement and expectancy using core strategies and principles of MI.…”
Section: Methodsmentioning
confidence: 99%
“…Heart rate variability (HRV) was used because it is an indicator of central nervous system activity and can differentiate between an 'affiliative' state (high HRV) and a 'threatened' state (low HRV) (Porges, 2006), and because brief CFI can stimulate increased HRV in healthy individuals (Rockliff, Gilbert, McEwan, Lightman, & Glover, 2008). Second, by promoting engagement in therapy using video-based information on psychological therapy to reduce pre-therapy state anxiety and to promote engagement and adherence; there is evidence to support this strategy from studies in adult mental health (Deane, Spicer & Leathem, 1992) and on preparing people with head injury for CBT targeted at anxiety (Hsieh, Wong, Schönberger, McKay, & Haines, 2012). Video-based delivery allows psychoeducational issues to be addressed uniformly across participants and can include familiarisation with key concepts and terminology in a way that circumvents common cognitive deficits after SHI.…”
Section: Introductionmentioning
confidence: 99%
“…Of those studies utilising this technique, MI was either found not to be more effective than goal setting alone (Corrigan et al, 2005) or its effects were not sufficiently measured (Hsieh, Ponsford, Wong, Schönberger, Taffe & Mckay, 2012;Hsieh, Ponsford, Wong, Schönberger, Mckay & Haines, 2012). This appears to contradict the suggestion of others (Medley & Powell, 2010;Holloway, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported interventions using predominantly behavioural modification techniques (Hegel, 1988Zencius, Wesolowski, Burke & McQuade, 1989;Yuen, 1996;Manchester, Hodgkinson, Pfaff & Nguyan, 1997;Newell, 1997;Sohlberg, Lemoncello & Lee, 2011;Hufford et al, 2012), 5 studies primarily cognitive techniques (Pegg et al, 2005;Lane-Brown & Tate, 2010;Skidmore et al, 2011;Hsieh, Ponsford, Wong, Schönberger, Taffe & Mckay, 2012;Hsieh, Ponsford, Wong, Schönberger, Mckay & Haines, 2012) and 2 studies reported a mixture of the two (Corrigan, Bogner, Lamb-Hart, Heinemann & Moore, 2005;Corrigan & Bogner, 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%